Horse-shoeing: it's uses and abuses - Hayes, Lawrence Wilbur (My University, 1896)
Introduction: Man has placed himself at the head of the animal kingdom, and it is his proven place. But, without the aid of certain animals which he has domesticated the world would not have attained his eminence quite so rapidly. One of the animals that have done much toward aiding man is the horse. It has helped man to till the soil; it has hauled his loads, and carried man himself over hills and through valleys in the heat of battle. What has done to help the dumb brute who has been faithful to duty? Some men treat their horses as though they were machines without any fueling.
Citation: Hayes, Lawrence Wilbur. Horse-shoeing: it's uses and abuses. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Man; Horse; Horseshoeing; Theses; Manuscripts (documents)